2018
DOI: 10.1007/s00338-018-01758-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate composition of mucus from scleractinian corals from the central Red Sea

Abstract: Coral mucus is continuously released by most corals and acts as an important protective barrier and as a substrate for host-associated microbial communities due to its complex composition of carbohydrates, lipids, and proteins. On a reef scale, coral mucus functions as a particle trap, thereby retaining nutrients and energy in the ecosystem. Given the distinct environmental conditions in the Red Sea (high temperature, high salinity, high total alkalinity), we sought to investigate the carbohydrate composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…Such host-specificity of bacterial communities is consistent with many other studies profiling coral microbiomes [80][81][82][83]. The variation in bacterial community composition between coral taxa could be explained by different factors including (i) species-specific composition of exudates by different coral hosts to the SML (e.g., [84]), (ii) species-specific biochemical composition of coral SML itself [85][86][87][88]; (iii) vertical transmission of bacterial community from parents to offspring [89][90][91][92]. However, which of these factors likely drive differences among bacterial communities of northern Red Sea corals is difficult to discern from the available data.…”
Section: Coral-specific Bacteriasupporting
confidence: 88%
“…Such host-specificity of bacterial communities is consistent with many other studies profiling coral microbiomes [80][81][82][83]. The variation in bacterial community composition between coral taxa could be explained by different factors including (i) species-specific composition of exudates by different coral hosts to the SML (e.g., [84]), (ii) species-specific biochemical composition of coral SML itself [85][86][87][88]; (iii) vertical transmission of bacterial community from parents to offspring [89][90][91][92]. However, which of these factors likely drive differences among bacterial communities of northern Red Sea corals is difficult to discern from the available data.…”
Section: Coral-specific Bacteriasupporting
confidence: 88%
“…Members of the fucosidase GH95 and GH29 enzyme families are known to degrade fucoidan, a complex fucosaccharide prominent in brown algae [ 50 , 52 ]. Notably, arabino- and fucopolysaccharides also make up a significant proportion of coral mucus, a major component of DOM in coral reefs that sponges have been shown to utilise [ 53 , 54 ]. Supporting this observation, isotopic investigation of the fate of coral mucus and algal polysaccharides in sponges showed that the microbiome participates in metabolism of these compounds, particularly in sponges with high microbial abundance and diversity [ 4 , 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Copiotrophs are known to rapidly (re)populate carbon-rich environments such as the surface mucus layer (Nelson et al, 2013;McDevitt-Irwin et al, 2017;Cárdenas et al, 2018;Hadaidi et al, 2019) and as such may "drive" initial microbial repopulation dynamics. This makes the long(er)-term tracking of microbiome assemblage dynamics after transplantation important.…”
Section: Discussionmentioning
confidence: 99%